GE_GERICHTE A/3135/2021 vom 24. Februar 2020 - GE Cour de justice (2020)
DROIT D'ÊTRE ENTENDU;EXPERTISE;PERMIS DE CONDUIRE;RETRAIT DE SÉCURITÉ | LCR.23.al1; LCR.16.al1; LCR.14; LCR.15d.al1; LCR.16d.al1; OAC.28a.al1